OPTIMALISASI PENJUALAN NOKEN KULIT KAYU MENGGUNAKAN METODE SIMPLEKS DAN SOFTWARE POM-QM - Rumetna, Matheus Supriyanto; Lina, Tirsa Ninia; Rustam, Muhammad Yusuf; Sitaniapessy, Sarza Farila; Soulisa, Dinda Irdayani; Sihombing, Dedi Suheri; Kareth, Salomo; Kadiwaru, Yohanes (Computer Based Information System Journal, 2020)
The indigenous people of Papua consist of various tribes and have several different tribes, one tribe which is a traditional Papuan society called Noken. Mr. Meki Murpa is one of the craftsmen and noken sellers located at F. Kalasuat street, Sorong City, West Papua. The problem issued by the noken seller Mr. Meki Murpa is to determine the optimal amount of production of noken sales, so that the maximum sales profit is obtained. This problem can be solved by using the Simplex Method which is one part of the Program. POM-QM software for Windows to be more efficient in the calculation process. The results of the application of this method are to help noki sellers of Mr. Meki Murpa in making decisions, determine the amount of production and calculate the profit of the sale of noken in a period of one week accurately.